Deteksi, Isolasi, dan Identifikasi Avian influenza Subtipe H5N1 pada Unggas di Pulau Jawa, Indonesia Tahun 2016 (DETECTION, ISOLATION AND IDENTIFICATION OF H5N1 SUBTYPE AVIAN INFLUENZA IN POULTRY IN JAVA ISLAND, INDONESIA, 2016) - Hewajuli, Dyah Ayu; Dharmayanti, Ni Luh Putu Indi; Wibawan, I Wayan Teguh (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.496, 2018)
H5N1 subtype Avian influenza has harmed for poultry in Indonesia currently. Since clade 2.3.2 Avian influenza has been found in waterfowl from 2012, mortality of waterfowl has been occured until now. Change of extreme weather condition with high rainfall and flood, small poultry that does not adjust stricted biosecurity and without vaccination program, and chain sale of poultry on traders can increase case and transmission of Avian influenza in poultry. The objective of study was to isolate and identify Avian influenza on poultry in Central Java, West Java, East Java and Banten in 2016. The study was conducted by using Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) method to identify H5N1 subtype Avian influenza on poultry. The study was also conducted by isolation of H5N1 subtype Avian influenza from poultry into 9-11 days of embrionated chicken eggs. The study result represented that a number of 24 pool samples were positive reacted on RT-PCR with matrix primer, a total of 15 pool samples was positive reacted on RT-PCR with H5 primer and as many as 11 pool samples were positive reacted on RT-PCR with N1 primer. Two isolates of H5N1 subtype Avian influenza were isolated samples collected from the Serang City and six isolates of H5N1 subtype Avian influenza from Avian influenza case on waterfowl in Lamongan District. EID50 titer isolates of Avian influenza virus subtype H5N1 were > 10 8 . The conclusion of this study was H5N1 subtype Avian influenza detected on samples collected from cloacal, trachea swab and organs of poultry from Pekalongan District, Brebes District, Serang City, and Lamongan District in 2016. H5N1 subtype Avian influenza can be grown and isolated from samples collected of Serang City and Lamongan District in 2016. H5N1 subtype Avian influenza can be detected, isolated, and indentified in poultry in Java Island, Indonesia in 2016.
Keywords: Flu burung subtipe H5N1, unggas, RT-PCR, Isolasi, Titer EID50